Nearly Zero Energy Building Refurbishment A Multidisciplinary Approach - Pacheco Torgal, Fernando; Mistretta, Marina; Kaklauskas, Artūras; Granqvist, Claes G.; Cabeza, Luisa F.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
The recast of the Energy Performance of Buildings Directive (EPBD) was adopted by the European Parliament and the Council of the European Union on 19 May 2010. For new buildings, the recast fixes 2020 as the deadline for all new buildings to be “nearly zero energy” (and even sooner for public buildings – by the end of 2018). This book gives practitioner an important tool to tackle the challenges of building refurbishment towards nearly zero energy. This book is welcome at this time and sets the scene for professionals whether practitioners or researchers to learn more about how we can make whether old or new buildings more efficient and effective in terms of energy performance. .
Policy instruments: The case of Germany -- Built environment life cycle process and climate change -- Benefits of refurbishment -- Building energy prediction based on occupant behavior -- Uncertainty in refurbishment investment -- Energy performance of buildings: a comparison of standard assessment methods -- Life cycle energy performance evaluation.-Retrofit scenarios to shift nearly net ZEBs towards net ZEB target -- A multiple-case study of passive house retrofits of school buildings in Austria -- State-of-the art on retrofit strategies selection using multi-objective optimization and genetic algorithms -- Multiple criteria analysis of life cycle of energy-efficient built environment -- Toxicity issues: Indoor air quality -- Toxicity issues: Radon -- Ventilation rate: thermal efficiency and health aspects -- Insulation materials made with vegetable fibres -- High performance insulation materials -- Thermal energy storage technologies -- Phase change materials in nearly zero energy building refurbishment -- Nanogel windows -- Switchable glazing technology: Electrochromic fenestration for energy efficient buildings -- Solar photovoltaic/termal tecnologies: Their application in building retrofitting.
Keywords: Energy efficiency; Buildings—Design and construction; Building; Construction; Engineering, Architectural; Renewable energy resources; Energy Efficiency; Building Construction and Design; Renewable and Green Energy